ASSESSMENT OF THE IMPACT OF HIGHER EDUCATION ON POVERTY ALLEVIATION (Conferencea, 2022)
Higher education plays an important role in the growth, prosperity of the economy and the correct use of existing opportunities, its expansion. From the studies, it should be noted that education plays a central role in the development strategy for two reasons: First, the quantity and quality of education greatly affects the workforce, management and working conditions of most institutions. This does not negate the fact that education is the main factor in the development of the investment climate in human capital. Secondly, in order to ensure that all sectors of the economy benefit from macroeconomic growth, it is advisable to increase the number of students in higher education.